Prognostic role of the CDNK1B V109G polymorphism in multiple endocrine neoplasia type 1. Issue 7 (30th March 2015) - Circelli, Luisa; Ramundo, Valeria; Marotta, Vincenzo; Sciammarella, Concetta; Marciello, Francesca; Del Prete, Michela; Sabatino, Lina; Pasquali, Daniela; Izzo, Francesco; Scala, Stefania; Colao, Annamaria; Faggiano, Antongiulio; et al.
Abstract CDKN1B encodes the cyclin‐dependent kinase inhibitor p27/Kip1. CDKN1B mutations and polymorphisms are involved in tumorigenesis; specifically, the V109G single nucleotide polymorphism has been linked to different tumours with controversial results. Multiple endocrine neoplasia type 1 (MEN1) is a rare autosomal dominant syndrome, characterized by the development of different types of neuroendocrine tumours and increased incidence of other malignancies. A clear genotype–phenotype correlation in MEN1 has not been established yet. In this study, we assessed whether the CDKN1B V109G polymorphism was associated with the development of aggressive tumours in 55 consecutive patients affected by MEN1. The polymorphism was investigated by PCR amplification of germline DNA followed by direct sequencing. Baseline and follow‐up data of tumour types and their severity were collected and associated with the genetic data. MEN1‐related aggressive and other malignant tumours of any origin were detected in 16.1% of wild‐type and 33.3% of polymorphism allele‐bearing patients (P = NS). The time interval between birth and the first aggressive tumour was significantly shorter in patients with the CDKN1B V109G polymorphism (median 46 years) than in those without (median not reached; P = 0.03). Similarly, shorter was the time interval between MEN1 diagnosis and age of the first aggressive tumour (P = 0.02). Overall survival could not be estimated as 96% patients were still alive at the time of the study. In conclusion, CDKN1B V109G polymorphism seems to play a role in the development of aggressive tumours in MEN1.